Reselling of European option if the implied volatility varies as Cox-Ingersoll-Ross process - Pupashenko, M.; Kukush, A. (Інститут математики НАН України, 2008)
On Black and Scholes market Investor buys a European call option. At each moment of time till the maturity he is allowed to resell the option for the quoted market price. In Kukush et al. (2006) On reselling of European option, Theory Stoch. Process., 12(28), 75-87, a similar problem was investigated for another model of the market price. We propose a more realistic model based on Cox-Ingersoll-Ross process. Discrete approximation for this model is investigated, which is arbitrage–free. For this discrete model, a formula for penultimate optimal stopping domains is derived.